Social work and social reform: an arena of struggle - Abramovitz, Mimi (1998)
The profession of social work has the potential both to meet individual needs and to engage in social change. However, the profession's position between the individual and society often forces practitioners to choose between adjusting people and programs to circumstances or challenging the status quo. The twin pressures of containment and change have made social work an arena of struggle since its origins in the late 19th century. In honor of social work's centennial, this article examines the sources of the profession's prochange mandate and the structural factors that limit social work's ability to pledge itself to this stance permanently and recommends some steps social workers can take to recommit the profession to greater activism. Special attention is given to documenting the long but largely ignored history of social work activism. - Reproduced
Keywords: Social reform; Social work